Acupuncture Has a Positive Effect on Asthmatic Rats in a Glucocorticoid-Independent Manner. Issue 6 (December 2016) - Wang, Wen-Qian; Xu, Yu-Dong; Cui, Long-Ping; Yin, Lei-Miao; Wang, Yu; Liu, Yan-Yan; Yang, Yong-Qing
Background: There is some evidence to support the use of acupuncture as an alternative therapy for asthma. However, the mechanisms underlying its effects are not fully understood. We have reported previously that acupuncture has beneficial effects on asthma without changing the concentration of serum cortisol, although endogenous glucocorticoid (GC) plays an important role in regulating immune responses. Objective: In this study, bilateral adrenalectomy (removal of both adrenal glands) was performed in rats before asthma model induction to investigate whether acupuncture influences asthma in a GC-dependent manner. Methods: Adrenal-intact and adrenalectomised rats were injected with ovalbumin to induce asthma and then left untreated or treated with manual acupuncture (MA) at GV14, bilateral BL12 and bilateral BL13, or manual restraint without MA. Healthy and sham-adrenalectomised control groups were also included. Pulmonary resistance (RL ), serum concentrations of corticosterone, and eosinophil counts were measured at the end of the experimental course. Sera from adrenal-intact and adrenalectomised asthmatic rats treated with acupuncture were injected into untreated adrenal-intact and adrenalectomised asthmatic rats to investigate further the potential role of GC in the effect of acupuncture. Results: Acupuncture significantly decreased RL and eosinophil count in both adrenal-intact and adrenalectomised asthmatic rats. Moreover, administration of sera derived from acupuncture-treated adrenal-intact and adrenalectomised asthmatic rats attenuated the increase in RL and eosinophil count in both asthmatic models. Conclusions: Results of this study suggest that endogenous GC is not a key contributor to the effects of acupuncture on asthma, and that acupuncture may have potentially therapeutic effects on asthma in a GC-independent manner.